A new species related to Alona costata Sars, 1862 (Cladocera: Anomopoda: Chydoridae) from South Africa - Sinev, Artem Yu (Zootaxa, 2008)
A new species of the genus Alona (Cladocera: Chydoridae), related to Alona costata Sars, 1862 was found in the Drakensberg Mountains, South Africa. Alona natalensis sp. n. differs from all other species of the costata-group by its unique carapace sculpturing. The position of the new species within the genus and its morphological peculiarities are discussed. A key for the world fauna of the costata-group is provided. A. natalensis sp. n. is confined to the Eastern Escarpment area; all occurrences are located within the area with an effective temperature index below 14 ºC. A complex of five endemic species of Anostraca (Hamer & Brendonk, 1997) as well as four recently described species of Chydoridae and Ilyocryptidae are confined to this area. Unlike widely distributed related species, A. natalensis sp. n. seems to be a relict species as defined by Korovchinsky (2006), confined to the restricted mountainous habitats.